Packaging as an instrument of marketing mix - Anđelić Slavica (Trendovi u Poslovanju)
Marketing is the concept of business-oriented customers, in this concept, the design of products and services starts from the needs of consumers, and consumer satisfaction is set as a target of operation, in companies with marketing concept fully implemented, not only the marketing department cares about the consumers, but all employees, working with the awareness that they are working for consumers, in these enterprises, commitment to consumers especially applies to employees who are in direct contact with them. Marketing concept is gaining more and more supporters due to the achieved good results, but there is also a number of upgrades and enhancements of the basic idea.